Analisis Nutrisi Makanan Berbasis Mobile Menggunakan CNN dan Artificial Intelligence - Rahmani, Husain; Mulyana, Dadang Iskandar (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
The development of Artificial Intelligence (AI) technology has opened up new opportunities in various fields, including health and nutrition. This research aims to develop a mobile application that is able to analyze the nutritional composition of food automatically using the Convolutional Neraul Network (CNN) method. This application is designed to assist users in monitoring nutritional intake through the recognition of food images taken using a mobile device camera. The methodology used includes collecting food image datasets, training CNN models integrated into mobile platforms so that they can be used in real-time and user-friendly. Tests were conducted to measure the accuracy of food classification and the accuracy of estimating its nutritional composition.